ANALISIS PENGARUH KENAIKAN HARGA CABAI RAWIT TERHADAP KONSUMSI RUMAH TANGGA DI KOTA PALANGKA RAYA - Rifka Eliza Ambarita; Aisyah Mecca, Cryshanti Febri Timbang, Sumarianto, Vivi Rolensa, Justino Lumbantungkup (CV. Adiba Aisha Amira, 2024)
Introduction: This research discusses the analysis of the influence of increasing chili prices on household consumption in the city of Palangkaraya. The increase in chili prices often affects household consumption. If the price of chilies is above the normal price, then household consumers will reduce their consumption to reduce household expenditure. This is in accordance with the law of demand which is negative or opposite. Method: The method in this research uses quantitative methods which are analyzed using simple regression analysis tools. With two dependent and independent variables, namely price and household consumption. Using primary and secondary data obtained using direct questions and answers with cayenne pepper consumers and cayenne pepper production data obtained through BPS Palangkaraya City. Primary data was combined through direct question and answer or the researcher went out into the field to ask household consumers in two directions (face to face) and consumers answered directly to the questions given by the researcher. Meanwhile, secondary data was taken from the official BPS website for Palangka Raya City. Results: Explains that the increase in chili prices in Palangka Raya City has a significant impact on household consumption. Consumers will reduce their consumption of cayenne pepper when the price of chili is above the normal price. Meanwhile, consumption will remain the same when the chili price is at the normal price. However, if the chili price is below the normal price, chili consumption will remain the same or increase by a small percentage. Conclusion: Researchers confirm that this data is real data because it was obtained through direct experience by cayenne pepper consumers. And it can be concluded that price really determines household consumption of cayenne pepper.